Insights Into the Eruptive Dynamics of Small Caldera-Forming Eruptions: The Case Study of the Welded Scoriae of Vulcano (Aeolian Islands, Italy) - Nicotra, Eugenio; Minniti, Marta; Donato, Paola; De Rosa, Rosanna (Frontiers in Earth Science, 2020)
A multi-disciplinary study, integrating volcanological field observations, petrography, whole rock geochemistry and textural and compositional analyses on plagioclase crystals has been carried out on the products of Monte Luccia, Spiaggia Lunga, and Quadrara eruptions, occurred between 48 and 21 kyrs on the island of Vulcano. These products are all characterized by welded scoria blankets, and their eruptions have been generally related to the formation and/or re-activation of ring faults bordering the “Il Piano” caldera. The aim of the work is to reconstruct the pre- and syn-eruptive dynamics acting within their magma plumbing systems and the related link with the phases of caldera collapse. At the bottom of the stratigraphic sequences, the presence of base surge deposits suggests that all the eruptions started with a phreatomagmatic phase fed by a shallow reservoir. Textural and microanalytical study of plagioclase crystals of Spiaggia Lunga eruption revealed that the phreatomagmatic event activated the ascent of a volatile-rich, basaltic magma residing at 5–11 km of depth. This basaltic magma mixed with the resident shallow one, and was poured out during the course of the eruption producing a sustained lava-fountaining phase. The subsequent caldera collapse, identified by a layer of chaotic breccia interbedded in the scoriae deposit, has been linked to the partial emptying of the shallow magma reservoir. In contrast to what observed for recent eruptive events at Vulcano, the onset of the magmatic phase would be attributed to a self-activation due to volcano-tectonic events, and not to a pressurization of the plumbing system related to the ascent of deep magma batches. As concerns the Mt. Luccia deposits, bordering the eastern rim of the “Il Piano” caldera, the absence of plagioclase in the mineralogical assemblage suggests the eruption of a deeper magma (>11 km b.s.l.), rapidly ascending through the re-activated ring faults of “Il Piano” caldera. At Quadrara eruption, the occurrence of a layer of white biotite-bearing latitic pumices overlying the basal phreatomagmatic deposits suggests the involvement a shallow, isolated reservoir where the increase of volatile pressure allowed the crystallization of hydrous phases. A deeper shoshonitic magma was involved later in the eruption, forming the welded scoria level at the top of the sequence.